Pengaruh Modal Kerja dan Biaya Operasional Terhadap Laba Bersih PT Matahari Putra Prima, Tbk - Andarsita, Nila; Rendra Erdkhadifa (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This study was motivated by the decline in the company's net profit value at PT Matahari Putra Prima Tbk. One of the causes of the decline in the company's net profit is the high costs incurred by the company. Increased net profit plays an important role in the prosperity of the company and investors. If the net profit value generated by the company has good performance, it will be glimpsed by investors as an initial consideration in choosing a company that will be given investment. Therefore, researchers raised the issue of the effect of working capital and operating costs on net income. This research uses a quantitative approach with a descriptive type. The data used in this study is secondary data, the data source is obtained from the quarterly financial statements of PT Matahari Putra Prima Tbk from the period March 2015-December 2022. The sample of this study amounted to 32 samples of quarterly financial statements. The data analysis technique used is multiple linear regression analysis. The results showed that working capital has a positive relationship and partially has a significant effect on net income. Meanwhile, operating costs have a negative relationship and partially have a significant effect on net income.